Hukum Keluarga Islam di Indonesia: dari Orde Lama hingga Orde Reformasi - Rajafi, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2017)
Historically, the rule of Islamic family law existed and has been practiced since the early arrival of Islam in the archipelago. This is indicated by the phenomenon of massive application of fiqh madzhab asy-syafi’iyyah in the colonialization era.. After the day of Independence, the efforts to established Islamic family law through political institutions has begun, starting from the old order era until the reform era. The reform movement grew stronger mainly after CLD-KHI was echoed to make KHI ( Collection of Islamic Law) a new Marriage Act. Unfortunately, this movement received a negative response from a number of Islamic organizations; so the plan was canceled by the Government. Nevertheless, the struggles between liberal and conservative-fundamentalist Islamic thought still continue to this day.